Assessment of Litter Input, Decomposition and Elements Dynamics in Yatta Tropical Forest in Western Equatoria State, South Sudan (University of Khartoum Journal of Agricultural Sciences, 2022)
This study characterized soils, assessed litter input, litter decomposition and elements release in Yatta forest, Western Equatoria State, South Sudan during May 2008 and March 2010. The soil was described and sampled. Litter was collected weekly from plots of 16 m2 under the forest cover with forty replicates. Seventy five litter bags were buried at 15-30 cm soil depth to assess decomposition and elements' release. Twenty fife bags were withdrawn at every 6, 12 months periods   Fallen litter, remaining decomposed litter and soil samples were analyzed in the Laboratory of the Department of Soil and Environment Sciences, Faculty of Agriculture, University of Khartoum. The soil was characterized as Oxisols, sandy clay loam, acidic, rich in organic matter, and amply furnished with nutrients. Litter input was 1791 kg/ha/year; with concessive seasonal maxima and minima in dry and wet months. Losses of dry matter were high, ranging of 52.2 % to 96.8 % during the tested periods. The elements K, N, P, Ca, Mg were rapidly released with successive rates ranges of 37 %-62 %, 56 %-72 % and 62 %-90 % during 6, 12 and 18 months observation periods. The results showed a high potential fertility of this natural forest site which will support the sustainability of the growing stock and utilization of the forest for high yielding food crops.